Transcriptome and metabolome comprehensive analysis reveal the molecular basis of slow-action and non-repellency of cycloxaprid against an eusocial pest, Solenopsis invicta - Du, Chengju; Jiang, Kaibin; Xu, Zhiping; Wang, Lei; Chen, Jie; Wang, Cai (Frontiers in Physiology, 2023)
The eusocial pest, red imported fire ant (Solenopsis invicta), is a highly invasive species that poses significant threats to public safety, agriculture, and the ecological environment. Cycloxaprid, a newly identified effective, slow-acting, and non-repellent insecticide against S. invicta, allows contaminated individuals to transfer the insecticide among nestmates through body contact. However, the molecular-level changes occurring in S. invicta post cycloxaprid exposure and any molecular alterations contributing to the slow demise or decreased sensitivity remain unclear. In this study, transcriptomic and metabolomic techniques were used to investigate the molecular mechanisms of S. invicta exposed to cycloxaprid. Differential analysis results revealed 275, 323, and 536 differentially expressed genes (DEGs) at 12, 24, and 48 h, respectively. Genes involved in lipid and energy metabolism, DNA integration, and hormone synthesis were largely upregulated at 12 h, suggesting S. invicta might actively resist cycloxaprid impacts, and predominantly downregulated at 48 h, indicating further functional impairment and impending death. Also, we observed an imbalance in olfactory perception pathways at 12 h, which may indicate a disruption in the olfactory system of S. invicta. Metabolomic results showed that the regulation of most differential metabolites (DMs) was consistent with the expression changes of their related DEGs at different time points. Our study provides insights into the mechanism underlying slow-acting and non-repellent properties of cycloxaprid against S. invicta.